Work and life integration : organizational, cultural, and individual perspectives - Kossek, Ellen Ernst; Lambert, Susan J. (Organization and management series (Routledge (Firm)), 2005)
Addresses the intersect between work, life, and family; discusses current challenges in dealing with work-life integration issues and sets the stage for future research agendas.